Real‐world treatment patterns and oncological outcomes in early relapse and refractory disease after bacillus Calmette‐Guérin failure in non‐muscle‐invasive bladder cancer. (20th July 2022) - Murakami, Yasukiyo; Matsumoto, Kazumasa; Miyake, Makito; Amano, Noriyuki; Shimura, Soichiro; Nishimura, Nobutaka; Iida, Kota; Matsushita, Yuto; Abe, Takashige; Yamada, Takeshi; Uemura, Motohide; Matsui, Yoshiyuki; et al.
Abstract : Objective: To assess real‐world oncological outcomes between the radical cystectomy (RC) group and non‐RC group for early relapse and refractory disease. Methods: We retrospectively analyzed 953 patients with recurrent non‐muscle‐invasive bladder cancer (NMIBC) who received bacillus Calmette‐Guérin (BCG) at 31 affiliated hospitals from 2000 to 2019. Patients with missing data on the timing of failure were excluded and 871 patients remained eligible, of whom 447, 357, and 67 were classified as early relapse/refractory disease, intermediate/late relapse disease, and intolerant disease, respectively. For early relapse/refractory disease, patients were divided into two salvage treatment groups: RC and non‐RC. The clinicopathological variables of each group were examined using Kaplan–Meier plots and proportional Cox hazard ratios with matched score analyses to compare oncological outcomes between the two groups. Results: Significantly worse progression‐free survival and cancer‐specific survival (CSS) were confirmed in the early relapse/refractory disease group compared to the intermediate/late relapse group. Of the 88 salvage patients in the RC group with early relapse/refractory disease, ≤pT1 was observed in 47, pT2 in 11, and ≥pT3 in 28 (two patients with unknown pT category). In early relapse/refractory disease, the RC group showed significantly high‐risk tumor compared to the non‐RC group. However, no significant difference was observed in CSS after matched score analyses ( p  = 0.45) between the RC and non‐RC groups. Conclusions: This study found that the RC group showed no significant superiority compared to the non‐RC group in CSS for early relapse/refractory disease in terms of first salvage therapy.